Warm antibody hemolytic anemia—a rare presentation of neonatal lupus. (May 2017) - Halder, Rohan; Malik, Richa; Kashyap, Rajesh
Neonatal lupus erythematosus (NLE) affects 1%–2% pregnant females with autoimmunity. An infant presented with steroid refractory hemolytic anemia as a manifestation of NLE. A trial of withholding breastfeeding had a transient response, but infant was eventually put on cyclosporin therapy to control the hemolysis. Now he is thriving well and transfusion free.